2021
DOI: 10.3389/fpls.2021.627501
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of PPR Proteins in Organelle RNA Metabolism and Chloroplast Biogenesis

Abstract: The pentatricopeptide repeat (PPR) proteins constitute one of the largest nuclear-encoded protein families in higher plants, with over 400 members in most sequenced plant species. The molecular functions of these proteins and their physiological roles during plant growth and development have been widely studied. Generally, there is mounting evidence that PPR proteins are involved in the post-transcriptional regulation of chloroplast and/or mitochondrial genes, including RNA maturation, editing, intron splicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 91 publications
0
38
0
Order By: Relevance
“…Among the plant mitochondria, one frequently encounters trans-spliced introns where two initially separate transcripts become covalently joined through the splicing process. The mechanism of mitochondrial intron splicing is complex involving many splicing factors, which facilitate the trans-splicing of Group II introns, including pentatricopeptide repeat (PPR) proteins, chloroplast RNA splicing and ribosome maturation (CRM) proteins, RNA DEAD-box helicases, plant organellar RNA recognition (PORR) domain proteins, regulator of chromosome condensation (RCC) proteins, and others [192][193][194][195]. Among them, PPR, PORR, and RCC may act as the factors that recognize the specific RNA-binding sites [69].…”
Section: Maturase and Splicing Factorsmentioning
confidence: 99%
“…Among the plant mitochondria, one frequently encounters trans-spliced introns where two initially separate transcripts become covalently joined through the splicing process. The mechanism of mitochondrial intron splicing is complex involving many splicing factors, which facilitate the trans-splicing of Group II introns, including pentatricopeptide repeat (PPR) proteins, chloroplast RNA splicing and ribosome maturation (CRM) proteins, RNA DEAD-box helicases, plant organellar RNA recognition (PORR) domain proteins, regulator of chromosome condensation (RCC) proteins, and others [192][193][194][195]. Among them, PPR, PORR, and RCC may act as the factors that recognize the specific RNA-binding sites [69].…”
Section: Maturase and Splicing Factorsmentioning
confidence: 99%
“…As stated earlier, PPR-containing proteins bind RNA in a sequence-specific manner [3][4][5][6][7][8]38]. The 3D structures of PPR-RNA complexes revealed that multiple contact points are required in these interactions [5][6][7]39].…”
Section: Ppr Length and Clusteringmentioning
confidence: 57%
“…Genes or alleles identified as the basis of pCNI remain largely unidentified but nuclear encoded genes such as PPR, sigma factors and Whirly genes have been implicated (Wang et al 2021, Wei et al 2015, Isemer et al 2012. This makes sense, as these genes are all involved in expression and maintenance of the chloroplast.…”
Section: Evolutionary Consequences Of Cnimentioning
confidence: 99%
“…A recent study of the numerous interactome proteins required for proper plastome expression found that nuclear encoded PPR genes assist in ribosome assembly (Westrich et al 2012). PPR genes play major roles in many steps of plastome and ribosome development, (reviewed by Wang et al 2021) and are often targeted specifically at organelles (Barkan 2014). PPR genes also play a role in compensating for changes in plastid genes via RNA editing (Ichinose 2017, Small et al 2020), but suppressing errors in 'micro-homology', which may occur in Pelargonium plastomes due to the rearrangements and repeats, is the domain of the nuclear encoded Whirly genes (Maréchal et al 2009, Isemer et al 2012).…”
Section: Nuclear Genomic Genes Interacting With the Plastomementioning
confidence: 99%